ANTIBACTERIAL ACTIVITY TEST OF ETHYL ACETATE EXTRACT OF BANANA KEPOK (MUSA PARADISIACA L) AGAINST STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI BACTERIA BY AGAR DIFFUSION METHOD - Yogi Rahman Nugraha, Yogi Rahman Nugraha; N. Ai Erlinawati, N. Ai Erlinawati; Eri Susanti Dewi, Eri Susanti Dewi (Jurnal Medika Farmaka, 2023)
Bacterial infection is a health disorder that can be transmitted from one person to another. Bacteria that cause infectious diseases include Staphylococcus aureus and Escherichia coli. In the kepok banana hump, there are secondary metabolites such as saponins, glycosides and tannins that act as antibacterial. The purpose of this study was to determine the antibacterial activity of ethyl acetate extract of kepok banana weevil (Musa paradisiaca L.) against Staphylococcus aureus and Escherichia coli. The stages of the research began with the collection of materials, determination, processing of materials, making of ethyl acetate extraction, concentration of extracts, testing of antibacterial activity. The research method used a laboratory experiment using the disc diffusion method. Kepok banana weevil extraction was carried out using the maceration method with ethyl acetate, the antibacterial activity was tested using the agar diffusion method. The results of the antibacterial test against S. aureus bacteria in the ethyl acetate extract of kepok banana boggol (Musa paradisiaca L.) with concentrations of 0.3µg, 0.5µg, 0.6µg resulted in an average inhibition diameter of 7.1 mm, 7.7 mm, and 10.2 mm these three concentrations had an antibacterial effect in the category of resistant less than14 mm. In the positive control using the antibiotic chloramphenicol, an average inhibition zone of 21.3 mm was produced, including the Susceptible 19 mm category, while the negative control using ethyl acetate did not form an inhibition zone. In Escherichia coli bacteria At concentrations of 0.3 g, 0.5 g, 0.6 g of ethyl acetate extract of kepok banana boggol (Musa paradisiaca L.) the diameter of the inhibition zones averaged 6.9 mm, 7.6 mm, and 8.3. mm, these three concentrations had an antibacterial effect in the category of resistant less than 14 mm. In the positive control, chloramphenicol produced an average inhibition zone of 20.8 mm, including the Susceptible 19 mm category, while in the negative control using ethyl acetate, no inhibition zone was formed.